2018
DOI: 10.1158/1078-0432.ccr-17-2617
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of Newly Diagnosed and Recurrent Glioblastoma Defines Distinct Immune Exhaustion Profiles in Peripheral and Tumor-infiltrating Lymphocytes

Abstract: Immunotherapeutic treatment strategies for glioblastoma (GBM) are under investigation in clinical trials. However, our understanding of the immune phenotype of GBM-infiltrating T cells (tumor-infiltrating lymphocytes; TILs) and changes during disease progression is limited. Deeper insight is urgently needed to therapeutically overcome tumor-induced immune exhaustion. We used flow cytometry and cytokine assays to profile TILs and peripheral blood lymphocytes (PBLs) from patients with GBM, comparing newly diagno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 52 publications
10
109
3
Order By: Relevance
“…However, we favour TGF‐β as a modulator of the NK cell phenotype in GBM, as we show reduced expression of activation receptors coupled with increased expression of CD9, a tetraspanin induced by TGF‐β in NK cells . Mohme et al showed that infiltrating T cells expressed PD‐1, TIM‐3 and CD39 , characteristic of T cell exhaustion . Our analysis extended these findings by identifying CTLA‐4 and LAG‐3 on GBM‐infiltrating T cells.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, we favour TGF‐β as a modulator of the NK cell phenotype in GBM, as we show reduced expression of activation receptors coupled with increased expression of CD9, a tetraspanin induced by TGF‐β in NK cells . Mohme et al showed that infiltrating T cells expressed PD‐1, TIM‐3 and CD39 , characteristic of T cell exhaustion . Our analysis extended these findings by identifying CTLA‐4 and LAG‐3 on GBM‐infiltrating T cells.…”
Section: Discussionsupporting
confidence: 76%
“…a) and 5'‐nucleotidase ecto (NT5E) (encoding CD39) by the immune fraction (Fig. b), with Mohme et al demonstrating CD39 expression by GBM‐infiltrating T cells .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This scRNA-seq data along with the GSC surface antigen screen shows that both tumour and immune infiltrating cells express receptors and ligands that together constitute a complex network of immunosuppression. For example, the combined action of CD73 and CD39 generate immunosuppressive adenosine (29); our data shows expression of CD73 by the tumour cells ( Figure 3A) and NT5E (encoding CD39) by the immune fraction ( Figure 3B), with Mohme et al demonstrating CD39 expression by GBM infiltrating T cells (13).…”
Section: Surface Antigen Screening Of Gscs Identifies Candidate Immunsupporting
confidence: 57%
“…3 CMV can infect many cell types including and, like all herpes viruses, can result in life long persistence after the initial acute infection. 4 Therefore, the immunosuppression associated with GBM 5,6 would be the perfect environment for CMV re-activation in tumor cells. CMV DNA and protein products have been discovered in multiple tumor types 7-9 including low grade glioma and higher grade glioma (e.g.…”
Section: Introductionmentioning
confidence: 99%